M-WALLET TECHNOLOGY: PERCEPTION AND SATISFACTION OF USERS ON USAGE INTENSITY - Wulandari, Astri; Suryawardani, Bethani; Marcelino, Dandy (Jurnal Aplikasi Manajemen, 2020)
This study aimed to provide several purposes that could help LinkAja as an mwallet service provider to pay attention to consumer perceptions that will be impacted by user satisfaction and usage intensity. The research method used is quantitative with an explanatory approach and using the Structural Equational Model (SEM) as the analysis techniques with SMART PLS 2.0 software tools. This research was used accidentally as a sampling method with a total of 400 respondents. Based on the results calculations in the first sub-structure, consumer perception directly affects user satisfaction of LinkAja mobile wallet products. The research emphasizes the importance of consumer perceptions on mwallet satisfaction. From the calculation results in the second sub-structure, consumer satisfaction has an impact on the usage intensity of LinkAja m-wallet. Then this research shows a strong relationship between consumer perception and usage intensity of m-wallet And the last is consumer perception has a better impact on usage intensity of LinkAja mwallet through user satisfaction. For further researchers can modify this research by using different objects so that they can be compared to how consumer perceptions can affect user satisfaction and the intensity of using a digital wallet.